Introduction to political communications - Gaber, Ivor (Henry Stewart Talks, 2010)
Political communications defined, The public sphere, The 'democratic conversation', How does the media impact on the political process?, The media/politics nexus, The growth of 'spin', The political communications paradox, Obama's online campaign: a case study, Researching political communications, Agenda setting in UK elections, Overall conclusions